Sex differences in patients with acute coronary syndromes and non-obstructive coronary arteries: Presentation and outcome. (1st February 2023) - Williams, Matthew G.L.; Dastidar, Amardeep; Liang, Kate; Johnson, Thomas W.; Baritussio, Anna; Strange, Julian; Joshi, Nikhil; Dorman, Stephen; De Garate, Estefania; Spagnoli, Lucrezia; Fiori, Emiliano; Lawton, Christopher; et al.
Abstract: Background: A substantial number of patients present with a suspected ACS and non-obstructive coronary arteries; sex differences in these patients are not well understood. This study aims to evaluate the impact of sex on clinical presentation and outcome in patients with suspected acute coronary syndrome (ACS) and non-obstructive coronary arteries with a final diagnosis confirmed by cardiovascular magnetic resonance imaging (CMR). Methods: Consecutive patients with ACS and non-obstructive coronary arteries ( n  = 719) with an unclear cause from a single tertiary centre who were referred for CMR were included. The primary endpoint was all-cause mortality. Results: CMR was performed at a median time of 30 days after presentation and identified a diagnosis in 74% of patients. All-cause mortality was 9.5% over a median follow up of 4.9 years, with no significant difference between sexes (8.8% versus 10.1%; p  = 0.456). Men were more likely to have non-ischaemic aetiology on CMR than women (55% v 41%, p  < 0.001), but were equally likely to have an ischaemic cause (25% v 27%, p  = 0.462). Age group (HR 1.58, p < 0.001) and LV ejection fraction (HR 0.98, p  = 0.023) were independent predictors of mortality. Conclusions: There is no difference in all-cause mortality between sexes in patients presenting with suspected ACS and non-obstructive coronary arteries. Highlights: All-cause mortality was 9.5% over a median follow up of 4.9 years. There was no overall difference in mortality by sex. Mortality is highest in the non-ischaemic group in both sexes. Men were more likely to have a non-ischaemic aetiology on CMR driven by a higher incidence of myocarditis.